Aspects of cytomegalovirus reactivation in critically ill patients - V. V. Gorbachev; T. I. Dmitrachenko; V. M. Semenov; S. K. Egorov (Журнал инфектологии, 2022)
Cytomegalovirus plays an essential role in human pathology. Primary infection usually occurs in childhood and subsequently, a lifelong latency is formed which the virus replicates by evading the immune response. In recent years, more and more researchers have concluded that cytomegalovirus reactivation may occur in critically ill patients. Despite the available evidence, data on reactivation in this group of patients are limited by the relatively small sample size, the variety of patient groups studied, the differences in study methodology, and the variability in reported results, which excludes the possibility of summarizing the results.This study aimed to determine the frequency of reactivation of cytomegalovirus infection in critically ill patients and to identify its main clinical features.Materials and methods. The study included 118 critically ill patients with severe bacterial and viral-bacterial infections accompanied by multiple organ dysfunction. Cytomegalovirus reactivation was determined by the detection of DNA in combination with the presence of IgG.Results. Reactivation was detected in 36.4% of cases. Frequency and terms of reactivation in blood and sputum as well as trends of viral load changes in dynamics were shown. The main clinical features of reactivation in different pathologies (sepsis of bacterial etiology, COVID-19, non-septic critical patients) were noted. HCMV DNA was more frequently detected in the blood of septic patients (44.8%) compared with COVID-19 (13.0%, p<0.05) and non-septic critically ill patients (19.2%, p<0.05). COVID-19 was characterized not only by lower detection of HCMV DNA in the blood but also by the lowest viral loads (p<0.05). HCMV DNA in sputum was detected comparably frequently in sepsis (38.1%) and COVID-19 (33.3%), but the highest viral loads were characteristic of patients with sepsis (p<0.05).